Variant expression signatures of microRNAs and protein related to growth in a crossbreed between two strains of Nile tilapia (Oreochromis niloticus) - Herkenhoff, Marcos Edgar [UNESP]; Bovolenta, Luiz A. [UNESP]; Broedel, Oliver; dos Santos, Lucilene D. [UNESP]; de Oliveira, Arthur C. [UNESP]; Chuffa, Luiz G.A. [UNESP]; Ribeiro, Amanda de O. [UNESP]; Lupi, Luiz A. [UNESP]; Dias, Marco A.D.; Hilsdorf, Alexandre W.S.; Frohme, Marcus; Pinhal, Danillo [UNESP] (Elsevier, 2021)
Nile tilapia (Oreochromis niloticus) is a species of worldwide importance for aquaculture. A crossbred lineage was developed through introgressive backcross breeding techniques and combines the high growth performance of the Chitralada (CHIT) lwith attractive reddish color of the Red Stirling (REDS) strains. Since the crossbreed has an unknown genetically improved background, the objective of this work was to characterize expression signatures that portray the advantageous phenotype of the crossbreeds. We characterized the microRNA transcriptome by high throughput sequencing (RNA-seq) and the proteome through mass spectrometry (ESI-Q-TOF-MS) and applied bioinformatics for the comparative analysis of such molecular data on the three strains. Crossbreed expressed a distinct set of miRNAs and proteins compared to the parents. They comprised several microRNAs regulate traits of economic interest. Proteomic profiles revealed differences between parental and crossbreed in expression of proteins associated with glycolisis. Distinctive miRNA and protein signatures contribute to the phenotype of crossbreed.
Keywords: ESI-Q-TOF; Growth; miRNA; Nile tilapia; Proteome; RNA-Seq